EFEKTIVITAS GAME EDUKASI “MELADA” UNTUK MENINGKATKAN KETERAMPILAN BERNYANYI LAGU DAERAH - Salsabilla, Nathania Hellen; Zulfikasari, Sony (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Learning regional songs in elementary schools faces major challenges due to the massive dominance of popular digital culture and conventional, text-based learning methods, which cause low student motivation and skills. This study aims to examine the effectiveness of using the